Prediction of larval viability based on egg quality parameters and early cleavage patterns in the experiments of triploidy induction in Atlantic cod, Gadus morhua L. - Rani, Manira Sultana (Universitetet i Tromsø, 2005)
Abnormal blastomere morphology may be indicative of low egg viability in fish and therefore represent a useful tool for rapid qualitative assessments for commercial and experimental aquaculture purposes. This work reviews the literature on this subject, and compares early cleavage patterns in a series of preliminary experiments of triploidy induction in Atlantic cod, Gadus morhua. Data from 4 different egg batches showed that cleavage abnormalities were generally higher in cold-shocked groups than control groups, though significantly only in 2 out of 4 experiments. Cell asymmetry was the most common type of cleavage abnormality in all trials, whereas other patterns such as complete separation of blastomeres or cell asymmetry combined with unequal blastomere size were observed in some of the experiments only. There was no significant difference between control and treated groups in terms of survival at any of the developmental stages in all batches. Proportions of abnormal blastomeres were negatively correlated with survival at day 1 while no correlations were observed at embryonation or hatching. This work shows that cold shock treatments applied shortly after fertilization may significantly increase, in some cases, the number of cleavage abnormalities but without affecting general survival at hatching. This would indicate that cleavage patterns abnormalities may not be considered as a good indicator of egg larval viability in such experiments.